2017
DOI: 10.1007/s00277-017-2926-9
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of power Doppler ultrasonography-guided core-needle biopsy with open surgical biopsy for the characterization of lymphadenopathies in patients with suspected lymphoma

Abstract: The sensitivity of lymph node core-needle biopsy under imaging guidance requires validation. We employed power Doppler ultrasonography (PDUS) to select the lymph node most suspected of malignancy and to histologically characterize it through the use of large cutting needle. Institutional review board approval and informed consent were obtained for this randomized clinical trial. In a single center between 1 January 2009 and 31 December 2015, patients with lymph node enlargement suspected for lymphoma were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 20 publications
0
78
0
Order By: Relevance
“…A smaller previous study compared 14‐gauge CNB with SNE and found discrepant diagnostic results in 9.1% of cases . In another study, CNB and SNE were prospectively compared, and superiority was seen for CNB . Thus, a comparison of the diagnostic accuracy of SNE versus CNB or FCNB is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller previous study compared 14‐gauge CNB with SNE and found discrepant diagnostic results in 9.1% of cases . In another study, CNB and SNE were prospectively compared, and superiority was seen for CNB . Thus, a comparison of the diagnostic accuracy of SNE versus CNB or FCNB is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important issue regarding the generalizability of our results. For example, it is well established that interobserver variability and US experience have a major impact on results . In this study, all LN biopsies were performed by an examiner with greater than 35 years of US experience.…”
Section: Discussionmentioning
confidence: 99%
“…One main concern of FNAB/CNB is that findings may not be representative of the entire lesion, but the chances of missing a high-grade component can be reduced if clinical and radiological findings are correlated. A comparative study showed that power Doppler ultrasonography-guided CNB had better sensitivity for the detection of lymphoma in lymph nodes than open surgical biopsy [29]. This emphasizes the importance of imaging studies in the diagnosis of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…A histological diagnosis was available in 16 of 35 cases (45.7%): a core-needle cutting biopsy was performed in 12 cases under ultrasound guidance as previously described, 15 and an excisional biopsy in the remaining four cases. Clinical follow-up data were available for all patients.…”
Section: Histological-clinical Follow-up and Statistical Analysismentioning
confidence: 99%